(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
The study aimed to investigate PGR’s effect on in vitro grapes Vitis Vinifera L. cvs. Superior and Red globe single nodes propagation. During the surface sterilization stage (10, 20, and 30%), commercial bleach solution was used as a disinfectant agent for (5, 10, and 15 minutes) immersion periods. In the multiplication stage, explants were planted in Murashige and Skoog (MS) medium enriched with (1, 2, 3, and 4 mg L-1) of Benzyl Adenine (BA) concentrations and the control treatment was (BA-free). The rooting stage included cultivating plantlets from the multiplication stage on half-salt strength MS media supplied with (0, 0.5, 1, and 1.5 mg L-1) indole-3- butyric acid (IBA). The results showed that the highest percentage of uncontaminated explants was achieved in 20% of commercial bleach solutions used for a 10-minute immersion period (90 and 80% for Superior and Red Globe cultivars, respectively). The results of the multiplication stage showed that the highest values of newly formed shoots number and leaves number (4.50 and 20.90, respectively, for the Superior) and (4.10 and 18.50, respectively, for the Red Globe) were recorded in media containing 2 mg L-1 BA. The Superior variety showed the highest rooting percentage (90%) and significant root number (3.55) in a medium containing 1 mg L-1 IBA, while the Red Globe variety had the highest percentage (100%), and the root number (3.50) in the medium contained 0.5 mg L-1. The results of this study provide a rapid and effective propagative propagation system for selected grapes.